Answer:
The answer is statement D.
Explanation:
In order to determine the true statement, we have to solve every statement.
In any function, we replace any allowed "x" value and the function gives us a value. This process is called "evaluating function". If we want to compare different values of the function for different "x" values, we just have to evaluate them first and then compare.
So, for x=2 and x=3
f(2)=-3*(2)^2+4*2+6=-12+8+6=2
f(3)=-3*(3)^2+4*3+6=-27+12+6=-9
f(2)>f(3)
According to the possible options, the true statement is D.